The Cambridge history of Japan (Cambridge University Press, 1989)
One of the major transformations in world history during the twentieth century has been the slow shift of world economic and political power from the Atlantic to the Pacific Rim. Japan has played a key role in spurring this transformation. Once an isolated island society, little known to its neighbours and practically unknown to the West, Japan has emerged today as a leading economic power. The country's rise to a position of international prominence has not been a smooth process, however - it has come only after a period of turmoil and conflict. The Cambridge History of Japan is the first major collaborative synthesis to present the current state of knowledge of Japanese history for the English-reading world. Volume 6 provides a general introduction to Japan's history during the first three quarters of the twentieth century, with emphasis on political, economic, social and intellectual trends. Leading historians have contributed essays, based on recent Western and Japanese scholarship, dealing with the development of domestic politics, particularly the politics of representative institutions, and Japan's relations with the outside world, including its prewar territorial expansion and aggrandizement on the Asian continent. The essays also survey Japan's economic development, describe the changes that took place in the working and farming classes (which until recently constituted the majority of the Japanese population), and assess the ways in which intellectuals viewed these and other long-term social and economic changes. Although written by specialists, this volume will be an important reference work for general readers as well as scholars and students of modern Japanese history.